Outbreak of aseptic meningitis caused by echovirus 30 in Kushiro, Japan in 2017 - Maruo, Yuji; Nakanishi, Masanori; Suzuki, Yasuto; Kaneshi, Yosuke; Terashita, Yukayo; Narugami, Masashi; Takahashi, Michi; Kato, Sho; Suzuki, Ryota; Goto, Akiko; Miyoshi, Masahiro; Nagano, Hideki; et al. (Journal of Clinical Virology, 2019)
•There was an outbreak of aseptic meningitis caused by E30 in Kushiro, Japan.•A neutrophil predominance was shown in CSF samples in many patients.•Phylogenetic analysis showed the same cluster.•Genotype of E30 was more closely related to strains in Europe than those in Japan.•Standard precautions are considered essential to prevent the spread of E30 infection. Background: Echovirus 30 (E30) is one of the most common causative agents for aseptic meningitis. Objectives: In the autumn of 2017, there was an outbreak caused by E30 in Kushiro, Hokkaido, Japan. The aim of this study was to characterize this outbreak. Study design: Fifty-nine patients were admitted to the Department of Pediatrics, Kushiro Red Cross Hospital (KRCH) with clinical diagnosis of aseptic meningitis. Among those, 36 patients were finally diagnosed as E30-associated aseptic meningitis by the detection of viral RNA using reverse transcription-polymerase chain reaction (RT-PCR) and/or the evidence of more than four-fold rise in neutralizing antibody (NA) titers in the convalescent phase relative to those in the acute phase. We investigated these 36 confirmed cases. Results: The median age was 6 years (range: 6 months–14 years). The positive signs and symptoms were as follows: fever (100%), headache (94%), vomiting (92%), jolt accentuation (77%), neck stiffness (74%), Kernig sign (29%), and abdominal pain (28%). The median cerebrospinal fluid (CSF) white cell count, neutrophil count, and lymphocyte count were 222/μL (range: 3–1434/μL), 144/μL (range: 1–1269/μL), and 85/μL (range: 2–354/μL), respectively. Although the detected viral genes demonstrated same cluster, they were different from E30 strains observed in Japan between 2010 and 2014. Conclusion: We mainly showed clinical and virological features of the E30-associated aseptic meningitis outbreak that occurred in Kushiro. To prevent further spread of E30 infection, continuous surveillance of enterovirus (EV) circulation and standard precautions are considered essential.